TINGKAT INFLASI MEMODERASI HUBUNGAN FINANCIAL DISTRESS DAN GOOD CORPORATE GOVERNANCE TERHADAP HARGA SAHAM PERUSAHAAN DI INDONESIA - Ahmad Mustofa (2023)
This study aims to determine the effect of financial distress and good corporate governance on stock prices moderated by the inflation rate. The population of this study are transportation and logistics sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. This study used 123 samples obtained using purposive sampling method. The regression model used is panel data regression. The results of this study are that financial distress have a significant and negative effect on stock prices, independent commissioners have no a significant effect on stock prices, institutional ownership have no a significant effect on stock prices, and the inflation rate cannot moderate the effect of financial distress, independent commissioners, and institutional ownership on stock prices.